Fate and Toxicity of Carbamazepine and Its Degradation By-Products During Coupling of Ozonation and Nanofiltration for Urban Wastewater Reuse - Yacouba, Z. Amadou; Lesage, G.; Mendret, J.; Zaviska, F.; Petit, E.; Brosillon, S. (Frontiers in Environmental Chemistry, 2021)
Occurrence of emerging organic micropollutants in water bodies and their effects are a concern related to quality of reused water. Advanced oxidation processes have demonstrated promising results to address this challenge. Nonetheless, these processes may lead to the generation of more toxic oxidation by-products. The aim of this study was to investigate the coupling of ozonation and nanofiltration (NF) applied to carbamazepine (CBZ). It consisted in monitoring the degradation and fate of CBZ and its subsequent by-products, their fate and toxicity. CBZ was completely degraded after 5 min of ozonation and six identified transformation by-products were formed: I (hydroxycarbamazepine), BQM [1-(2-benzaldehyde)-4-hydro-(1H, 3H)-quinazoline-2-one], II (2-(1H)-quinazolinone), BaQM [1-(2-benzoic acid)-4-hydro-(1H, 3H)-quinazoline-2-one], BQD [1-(2-benzaldehyde)-(1H, 3H)-quinazoline-2,4-dione] and BaQD [1-(2-benzoic acid)-(1H, 3H)-quinazoline-2,4-dione]. Mineralization rate of ozonation never exceeded 12% even with high ozone dose. Bioassays with Vibrio fischeri revealed that BQM and BQD are responsible for toxicity. NF is able to remove total organic carbon with removal rate up to 93% at 85% of permeate recovery rate. CBZ and its different ozonation by-products were almost completely retained by NF, except the II, which had an MW slightly lower than the membrane molecular weight cut-off, for which the removal rate was still between 80 and 96% depending on the recovery rate.